2018
DOI: 10.1007/s00005-018-0515-9
|View full text |Cite
|
Sign up to set email alerts
|

Deviations in Peripheral Blood Cell Populations are Associated with the Stage of Primary Biliary Cholangitis and Presence of Itching

Abstract: To evaluate the role of Th17, Treg cells, activated T CD3+ and B CD19+ lymphocytes in primary biliary cholangitis (PBC) patients. 40 female patients with PBC and 20 healthy donors were enrolled in this study. The percentages and absolute counts of Th17, Treg, activated T CD3+, B CD19+, NK, NKT-like lymphocytes were measured by flow cytometry. Our research revealed significantly lower frequencies and absolute counts of CD4+CD25+FOXP3+ Treg cells (p < 0.0001), higher percentages and absolute counts of Th17 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Studies in other autoimmune liver diseases, such as primary biliary cirrhosis (PBC) or primary sclerosing cholangitis (PSC), have also provided evidence that the intrahepatic Tregs may be affected by the unique microenvironment of AIH. Unlike in AIH, peripheral and intrahepatic Tregs have long been well-documented to be numerically and functionally defective in patients with PBC and murine models of PBC (119)(120)(121). Gershwin et al has confirmed the important role of Treg deficiency in the initiation of PBC, which may be due to the loss of the IL-2 receptor alpha (IL2RA) gene (122)(123)(124).…”
Section: Tregs In Other Autoimmune Liver Diseasesmentioning
confidence: 99%
“…Studies in other autoimmune liver diseases, such as primary biliary cirrhosis (PBC) or primary sclerosing cholangitis (PSC), have also provided evidence that the intrahepatic Tregs may be affected by the unique microenvironment of AIH. Unlike in AIH, peripheral and intrahepatic Tregs have long been well-documented to be numerically and functionally defective in patients with PBC and murine models of PBC (119)(120)(121). Gershwin et al has confirmed the important role of Treg deficiency in the initiation of PBC, which may be due to the loss of the IL-2 receptor alpha (IL2RA) gene (122)(123)(124).…”
Section: Tregs In Other Autoimmune Liver Diseasesmentioning
confidence: 99%
“…Meanwhile, evidence continues to show that ETS-1 plays an important role in regulating the differentiation and development of immune cells such as T-cell differentiation into helper T lymphocytes 12 , B cell into plasma cells 13 , and the expression of cytokine and chemokine genes 33 in a wide variety of different cells. Presented study demonstrated the correlation between PBC course and peripheral blood subpopulations, namely, the numbers of Treg cells reduced and Th17 cells increased could be responsible for the loss of immune tolerance, autoimmune process, inflammatory development, and liver fibrosis in PBC, and the progression of the disease might be the cause of Th17 cell activation and the release of IL-17 11 . Therefore, ETS-1 might play a crucial role in occurrence and development of PBC.…”
Section: Discussionmentioning
confidence: 77%
“…To date, identified gene loci suggest that T lymphocyte differentiation plays a role in the development of PBC 10 . Pathological appearance of PBC is closely connected with peripheral blood cell subpopulations, especially T-regulatory (Treg) and T-helper 17 (Th17) lymphocytes, and both Treg and Th17 cells might play a crucial role in the pathogenesis and treatment of PBC 11 . E26 transformation specific sequence-1 (ETS-1) is a transcription factor that regulates the expression of various genes, including growth factors, chemokines and adhesion molecules, and it has been well demonstrated that ETS-1 plays a critical role in the proliferation and differentiation of immune cells such as T-cell differentiation into helper T lymphocytes 12 , and B cell into plasma cell 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies of circulating lymphocytes in PBC have observed increases in CD19+ B cells and activated CD25+ B cells, correlating with disease stage (73,97). Within the B cell compartment, different B cells subsets seem to be altered including decreased circulating memory B cells and increased naïve B cells and PBs (73,98).…”
Section: B Cell Expansion and Activation In Pbcmentioning
confidence: 99%